2015
DOI: 10.1128/aac.04231-14
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Resistance to Drug Combinations in Leishmania donovani: Metabolic and Phenotypic Adaptations

Abstract: f Together with vector control, chemotherapy is an essential tool for the control of visceral leishmaniasis (VL), but its efficacy is jeopardized by growing resistance and treatment failure against first-line drugs. To delay the emergence of resistance, the use of drug combinations of existing antileishmanial agents has been tested systematically in clinical trials for the treatment of visceral leishmaniasis (VL). In vitro, Leishmania donovani promastigotes are able to develop experimental resistance to severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
40
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 69 publications
4
40
0
Order By: Relevance
“…It remains to be established whether this accumulation is a consequence o (i) a lower rate of proline metabolism, (ii) a lack of correlation of RNA and protein expression levels, or (iii) its connection with arginine levels. Interestingly, higher proline levels were associated with playing a protective role against antimonialinduced, but not HePC-induced, oxidative stress (57). Metacyclogenesis accounts for the transformation of poorly infective procyclic promastigotes into highly infective metacyclic promastigotes.…”
Section: Discussionmentioning
confidence: 99%
“…It remains to be established whether this accumulation is a consequence o (i) a lower rate of proline metabolism, (ii) a lack of correlation of RNA and protein expression levels, or (iii) its connection with arginine levels. Interestingly, higher proline levels were associated with playing a protective role against antimonialinduced, but not HePC-induced, oxidative stress (57). Metacyclogenesis accounts for the transformation of poorly infective procyclic promastigotes into highly infective metacyclic promastigotes.…”
Section: Discussionmentioning
confidence: 99%
“…On an annual basis 1-2 million and ∼250 million people are reported to be infected with Leishmania (World Health Organization, 2008, Pigott et al., 2014) and Schistosoma parasites, respectively (Colley et al., 2014). Although drugs for each of these parasitic infections are available, prevention and treatment is often difficult due to side-effects (Sundar and Chakravarty, 2015) or ineffective due to drug-resistant parasites (Croft et al., 2006, Dondorp et al., 2009, Dondorp and Ringwald, 2013, Berg et al., 2015, Takala-Harrison et al., 2015). There is no vaccine that is clinically available or widely effective for any of the human parasitic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…S-adenosylmethionine syntethase is downregulated (0.461-fold change) in transgenic lines and from this we may infer that the levels of its substrate, AdoMet, part of the trans-sulfuration pathway, may also be affected. Changes in AdoMet production have been identified in drug resistant Leishmania and a correlation with oxidative stress has been established [49]. The second protein identified in our comparative proteomics analysis (Fig.…”
Section: Discussionmentioning
confidence: 74%
“…Several studies have pinpointed mitochondrial-dependent apoptosis and generation of ROS as major effectors in the mechanism of action of HePC [48, 49]. We measured superoxide accumulation with the fluorescent dye MitoSox (indicative of ROS levels in the mitochondria) under low pH and high temperature, and showed that transgenic parasites overexpressing HSPA9B are more susceptible to oxidative stress damage (Fig.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation